Cooperativismo de plataforma: a proposta de um modelo de negócios de uma cooperativa de plataforma no ramo de hospedagem - Vieira, Luiz Santos (Universidade do Vale do Rio dos Sinos, 2021)
The platform economy has modified different market segments, implementing technology to create and exchange value between producers and consumers. Unlike pipeline company models, in which transactions take place in a linear value chain format, digital platforms are able to present several interaction variables between the parts involved, making them more dynamic and competitive. In this context, the platform cooperativism seeks to bring a collective ownership and democratic management approach to new technology-based businesses. This new perspective of cooperativism is already widespread in practice in a lot of countries, while there are still few experiences applied in Brazil. It can, therefore, be inferred, based on such evidence, that there are some challenges to making the cooperative platform model viable in Brazil. In order to understand these factors, this master thesis has the general objective of proposing an artifact of a cooperative platform in the hosting industry to generate value for the members of credit unions. The choice of the accommodation sector was motivated by the possibility of generating income for members, in addition to the inclusion of aspects of social and environmental impact, to promoting local development and sustainable tourism. The connection with credit unions has the advantages of a large number of members and their affinity with cooperativism, if compared to the general population and, additionally, the possibility of accessing financing alternatives for the cooperative platform under study. Design science research was used as a research methodology, with a qualitative approach and following the steps of construction and validation of the artifact. For a better understanding of the context of platform cooperativism in Brazil, a questionnaire was applied to eight experts in platform cooperativism, to identify the challenges for the implementation. The canvas business model was used as a validation of the artifact in interviews with four intrapreneurs of a credit union, a travel industry startup CEO and a sustainability consultant. In the last stage of validation, three managers of credit unions, linked to the areas of: innovation, sustainability and strategic business, were interviewed. Finally, a business model of a hosting cooperative platform, resulting from the research, is presented, capable to increase value for the platform's stakeholders, and generating a positive impact on communities.
Keywords: Cooperativismo de plataforma; Modelo de negócios; Economia de plataforma; Cooperativa de crédito; Platform cooperativism; Business model; Platform economy; Credit union; ACCNPQ::Ciências Sociais Aplicadas::Administração